THEORETICAL ASPECTS OF IRRIGATION OF AGRICULTURAL CROPS - Sadullaev , Azamat Nafiddinovich; Narzullayev , Iskandarjon Ubaydulla o‘g‘li; Eshmanov , Husniddin Narzulla o‘g‘li (Educational Research in Universal Sciences, 2024)
This article delves into the theoretical underpinnings of irrigation practices for agricultural crops, providing a comprehensive exploration of the principles governing water management in the context of sustainable agriculture. Theoretical frameworks encompassing soil-water dynamics, plant physiology, and climatic variables are scrutinized to elucidate the intricate relationships influencing optimal irrigation strategies. The synthesis of these theoretical aspects aims to enhance our understanding of irrigation’s role in maximizing crop yields while minimizing resource utilization. Additionally, the article examines emerging technologies and methodologies that leverage theoretical insights to improve irrigation efficiency, contributing to the development of precision agriculture.